Effects of Low Temperature Stress on Spikelet-Related Parameters during Anthesis in Indica–Japonica Hybrid Rice - Zeng, Yanhua; Zhang, Yuping; Xiang, Jing; Uphoff, Norman T.; Pan, Xiaohua; Zhu, Defeng (Frontiers in Plant Science, 2017)
Poor spikelet fertility under low temperature (LT) stress during anthesis limits the possibility of high yield potential in indica–japonica hybrid rice, leading to reduced stability of grain yield. However, the cause for it is still unclear. In this study, three indica–japonica hybrid rice cultivars, Yongyou9, Yongyou17 (both cold sensitive), and Yongyou538, and one japonica inbred rice cultivar, Zhejing88 (cold tolerant), were grown under LT (17°C) and ambient temperature (AT) (25°C) during anthesis to test for their response with respect to spikelet fertility, pollen germination, and spikelet flowering. The results indicated that LT resulted in lower spikelet fertility in cold-sensitive cultivars than in cold-tolerant cultivars. Spikelet fertility was highly correlated with pollen germination on the stigma. The number of pollen grains and germinated pollen were higher in cold-tolerant cultivars than in cold-sensitive cultivars. Pollen fertility and pollen diameter were also higher in cold-tolerant cultivars, although the latter could achieve a high number of spikelets at anthesis in flowering patterns throughout the duration of LT stress. There were signiﬁcant differences in anther width and volume between genotypes and treatments according to microscopic analyses, but no differences were observed in anther dehiscence. Moreover, variation in the number of pollen grains on stigmas and in spikelet fertility was not related to either the number of spikelets reaching anthesis or anther dehiscence. Overall, improved anther size, better pollen function, and higher spikelet fertility under LT stress were observed in cold-tolerant cultivars than in cold-sensitive cultivars. The results suggest that the increase in spikelet fertility is due to enhanced pollen germination rather than the number of spikelets reaching anthesis.